Household resilience and its role in sustaining food security in rural Bangladesh - Ismat Tasnim; Md. Asif Iqbal; Ismat Ara Begum; Mohammad Jahangir Alam; Morten Graversgaard; Paresh Kumar Sarma; Kiril Manevski (PLoS ONE, 2025)
Food insecurity and agriculture in South Asia, including Bangladesh, pose significant threats to the well-being and livelihoods of its people. Building adaptive capacities and resilient food systems is crucial for sustainable livelihoods. This study employs the Resilience Index Measurement and Analysis II framework to construct a Resilience Capacity Index (RCI) and analyze its relationship with food security using data from the Bangladesh Integrated Household Survey 2018. The study applies Exploratory Factor Analysis and Structural Equation Modeling to examine the impact of key resilience components such as Access to Basic Services, Adaptive Capacity, and Assets on household resilience. The findings reveal that access to basic services, land assets, and farm equipment positively influences households’ resilience capacity. However, the presence of livestock assets has a negative impact, potentially due to market volatility, climate vulnerability, and disease outbreaks. Additionally, adaptive capacity has a positive but insignificant influence on RCI, suggesting that without enhancing economic opportunities, institutional support, and inclusive development strategies, adaptive capacity could not be enough to foster resilience. However, resilient capacity enhances food security metrics such as the Food Consumption Score and Expenditure. These findings underscore the importance of policies that focus on increasing and maintaining access to basic services, promoting sustainable land management practices, and strengthening social safety nets. This study emphasizes the importance of focusing on livestock assets to ensure their sustainability by stabilizing the livestock market, improving veterinary services, and providing subsidies to reduce maintenance costs.